AWEARNESS OF CERVICAL CANCER AND SCREENING AMONG COMMERCIAL SEX WORKER IN KEDAMAY WEYANE SUB CITY MEKELLE ETHIOPIA 2017/18 - Kassa, Mekuria; Tadesse, Haftom (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Cervical cancer is the commonest cancer affecting reproductive organ and also leading cause of death from cancer among women. It was estimated that 20.9 million women was at risk of developing cervical cancer in Ethiopia. The aim of this study was to assess the knowledge, attitude and practice of cervical cancer and screening among commercial sex workers in Kedamyweyane, sub city Mekelle.Method: Community based cross sectional study was conducted from April -May, 2017, Convenient sampling technique was used to get a total 277sample of commercial sex workers data was collected by using semi-structured questionnaire the data was analyzed using SPSS.version  20 descriptive and analytical statistics was conducted.Result: A total of 277 commercial sex workers participated in the study with response rate of 100%. From those 61(28.62%) heard of cervical cancer and 149(56.87%) did not know the risk factor and prevention method. And also 46(16.6%) had cervical cancer screening test. From all the respondents 129(49.23%) of them are thinking Carcinoma of the cervix cannot be transmitted from one person to another through unsafe sexual intercourse. Regarding treatment options, 173(66.03%) did not know any type of treatment option.Conclusion: More than half of Women have positive attitude towards cervical screening whereas the practice of cervical cancer Screening was generally very low however; their willingness to practice cervical cancer screening was high. Regarding risk factors, cause and prevention methods are still very low.